The ahl al-sunnah wa al-jama’ah factor and the rise of sufi institutions - Spahic, Omer (International Islamic University Malaysia, 2013)
There are two types of Sufism: authentic and pseudo, or theosophical, Sufism. Authentic Sufism is a product of Islam alone and is nothing else but the quintessence of orthodox Islam. Pseudo, or theosophical, Sufism, on the other hand, is an abominable innovation which was influenced by alien-to-Islam worldviews and traditions. The factors that influenced the rise of Sufi institutions approximately towards the end of the 3rd AH/ 9th CE century were the Turkish factor, the Persian factor, the Shi’ah factor, and the ahl al-sunnah wa al-jama’ah factor. This paper examines the role of the ahl al-sunnah wa al-jama’ah factor in expediting the proliferation of the phenomena of Sufism and Sufi institutions. The paper shows that the ahl al-sunnah wa al-jama’ah factor was the most important one in that it entailed more than a few political and social dimensions which proved critical for the development of both Islamic society and culture, and Sufism and the Sufi community. The main thrusts of the paper are the significance and evolution of the concept of ahl al-sunnah wa al-jama’ah and its relationship with the evolution of major Sufi institutions.